PEKAT KEBIJAKAN DALAM MENDUKUNG PERBANKAN SYARIAH - Mohammad Irwansyah Panjaitan (Jurnal Ilmiah Cano Ekonomos, 2017)
This study is merely a description with reference to some of the literature that has terkai theme of Islamic banking. Support development of Islamic banking by the Government to issue a "V Package of Economic Policy". Strength, which is owned by the institute of Islamic banking in Indonesia through law and policy economists V package is including; residents of predominantly Muslim Indonesia, commitment and support from the government, the support of the overall Islamic financial institutions incorporated in the Islamic world, and the concept inherent (build-in concept) Islamic bank in accordance with the needs of development. Weakness, which is perceived; controversy over the existence and operational system of Islamic banks, still lack understanding of the community about the product and the benefits of Islamic banking (an average of just 11%), the limited service network of Islamic banks and has not yet reached all the centers of economic activity, the success of the sharing system is highly dependent the honesty of customers and islamic banks are very vulnerable to those who in good faith, so require accuracy calculate the results, especially for the customers / members that the number of deposits were never fixed, the sharing system is in need of accuracy in counting compared with conventional systems, and islamic banks are still relatively new so it still takes time for the people to adapt.